Political Reality in Indonesia from the Perspective of Vilfredo Pareto - Muhammad Sifa Fauzi Yulianis; Widia Ari Susanti (Rechtsvinding, 2026)
According to Wilfredo Pareto, a sociologist, history demonstrates a continuous circulation of elites. This circulation occurs through two processes: the movement of individuals from lower social strata to higher social strata, and the replacement of governing elites by previously non-governing elites. When an elite group enters a position of political power, another elite group must leave that position. However, social theories such as Pareto’s elite circulation theory often encounter contradictions when confronted with empirical realities. The same situation occurs with Wilfredo Pareto’s theory of elite circulation when it is examined within the context of political reality in Indonesia. Empirical evidence indicates that political parties in Indonesia have not experienced effective elite circulation; instead, they tend to demonstrate practices of dynastic politics. This phenomenon can be observed during general elections and regional elections, where political candidates often consist of the same individuals or groups repeatedly. This study aims to examine Wilfredo Pareto’s elite circulation theory, analyze criticisms from other sociologists regarding Pareto’s theoretical perspective, and investigate how Pareto’s theory applies within Indonesian society. This research employs a library research method, namely research conducted by collecting relevant literature regarding Wilfredo Pareto’s elite circulation theory and subsequently describing and analyzing the collected data. The results indicate that, according to Pareto, political and governmental systems should experience changes, rotation, and movement among elites. Nevertheless, when applied to the Indonesian political context, Pareto’s theory appears to contradict reality. Indonesia demonstrates characteristics of dynastic politics, where individuals who are able to access political leadership and governmental positions are frequently those who possess close relationships with political party leaders. Consequently, political candidates in democratic processes such as elections and regional elections tend to remain unchanged, resulting in limited elite circulation.